Extremely loud & incredibly close [book club bag] - Foer, Jonathan Safran, 1977- (Houghton Mifflin, 2005)
Meet Oskar Schell, an inventor, Francophile, tambourine player, Shakespearean actor, jeweler, pacifist, correspondent with Stephen Hawking and Ringo Starr. He is nine years old. And he is on an urgent, secret search through the five boroughs of New York. His mission is to find the lock that fits a mysterious key belonging to his father, who died in the World Trade Center on 9/11. An inspired innocent, Oskar is alternately endearing, exasperating, and hilarious as he careens from Central Park to Coney Island to Harlem on his search. Along the way he is always dreaming up inventions to keep those he loves safe from harm. His goal is hopeful, but the past speaks a loud warning in stories of those who've lost loved ones before. As Oskar roams New York, he encounters a motley assortment of humanity who are all survivors in their own way. Ultimately, Oskar ends his journey where it began, at his father's grave. But now he is accompanied by the silent stranger who has been renting the spare room of his grandmother's apartment. They are there to dig up his father's empty coffin.